A testing tool visualizing and ensuring data-flow coverage - Laura Troost (University of Münster, European Research Center for Information Systems (ERCIS), 2024)
According to different studies, data-flow coverage is more effective in exposing errors than common control-flow metrics. However, there are not many suitable and available data-flow analysis tools. This report illustrates the technical details of the implementation of Dacite (Data-flow Coverage for Imperative Testing). Dacite is an open-source tool able to dynamically derive the covered data flow of a given Java program and its JUnit test cases. Using the Language Server Protocol, it visualizes the data flow within common IDEs. Moreover, Dacite provides feedback about the not-covered data flow and automatically generates test cases for these by using symbolic execution.
Keywords: 650; Data-Flow Analysis; Bytecode Instrumentation; Language Server Protocol